(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: The National Crime Record Bureau and the Prison Statistics India, 2020 report on the overcrowding and occupancy in jails has ripple effect on the spread of the COVID-19.The protection to health freedoms of detainees and prisoners reflected in the World Health Organization (WHO) Guidance on COVID-19 for Prisons and Detention, 2020. The Indian jails have congestion and inhabitance and prone to contagion disease. The COVID-19 has an expanding transmission among detainees in prisons, jails and detention homes. Objectives: The WHO Guidance on COVID-19 for Prisons and Detention, 2020 standardizes the essential instrument to manage the COVID-19 difficulties in penitentiaries and confinement homes. The direction secures the strength of detainees and convicts living in encased conditions. The ostensible purpose is to contain the COVID-19 disease from spreading to general population and release the under trials for the safe healthy conditions. Methodology: The methodology applied the canons of statutory interpretation of United Nations Principles of the Protection of Prisoners, 1982 and Basic Principles for the Treatment of Prisoners, 1990 alongside the Moscow Declaration on Prisons and Health, 2003 and Nelson Mandela Rules, 2015 in fostering the health equity and criminal justice during COVID-19 pandemic. The mandate of the WHO Interim Guidance on COVID-19 in Prisons and Other Places of Detention, 2020 is straight out in preventive and medicinal measures for the penitentiaries and confinement homes in the virus of COVID-19. Results: The paper tracks the salubrious results of the international legal norms and national precedents of High Courts and Supreme Court in heralding systemic prison reform. The compliance of WHO Interim Guidance on Preparedness, Prevention and Control of COVID-19 In Prisons and Other Places of Detention, 2020 cultivated robust criminal administration during COVID-19 pandemic and the lockdown in India. Conclusion: The judgment of High Courts and Supreme Court on prison reform during the COVID-19 pandemic in India has resulted in Health Rights of Prisoners and Prison Law Reforms during COVID-19 Pandemic in India. It also refurbished the medical services in correctional facilities and confinement homes in criminal justice system. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 893-900